2011
DOI: 10.1590/s1807-59322011001200023
|View full text |Cite
|
Sign up to set email alerts
|

Protective measures against ultrafiltration failure in peritoneal dialysis patients

Abstract: Ultrafiltration failure in patients undergoing peritoneal dialysis is a condition with an incidence that increases over time. It is related to increased cardiovascular morbidity and mortality and is a major cause of the abandonment of the treatment technique. Because the number of patients undergoing renal replacement therapy is increasing with society aging and because approximately 10% of this population is treated with peritoneal dialysis, this matter is becoming more common in everyday practice for clinici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 101 publications
(84 reference statements)
1
8
0
Order By: Relevance
“…The hyperglycemia-induced microvascular changes in the peritoneal membrane were mostly prevented by application of monoclonal anti-VEGF antibodies, while treatment with non-specific control antibodies was not effective. These experimental findings confirmed that VEGF plays an important role in glucose-induced neoangiogenesis and hyperpermeability of the peritoneal membrane in long-term PD [2,3,6].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The hyperglycemia-induced microvascular changes in the peritoneal membrane were mostly prevented by application of monoclonal anti-VEGF antibodies, while treatment with non-specific control antibodies was not effective. These experimental findings confirmed that VEGF plays an important role in glucose-induced neoangiogenesis and hyperpermeability of the peritoneal membrane in long-term PD [2,3,6].…”
Section: Discussionsupporting
confidence: 71%
“…Angiogenesis is the formation of new blood vessels from pre-existing endothelium. Some angiogenetic factors, such as VEGF, are increased in uremic conditions and upon exposure to high glucose solution during PD [6].…”
Section: Introductionmentioning
confidence: 99%
“…The long-term PD-associated progressive peritoneal membrane injury resulting in sterile peritoneal inflammation and fibrosis has been well documented. 5,6 The prolonged exposure to conventional PDS has been demonstrated to substantially contribute to peritoneal membrane injury and chronic low-grade inflammation 26 and a number of biomarkers have been evaluated in an attempt to help improve PD patient outcomes. 27 Acidic pH, high glucose concentrations and high levels of glucose degradation products in PDS have all been reported to cause local inflammation with resultant adverse functional outcomes, such as higher peritoneal solute transport rate (PSTR) and membrane failure due to fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of UF increases with duration of PD, so that 30-50% of patients with PD develop UF, many patients abandon PD due to UF, and dropout increases depending on the type of PD. It has been reported up to 3% of dropouts during the first year and 31% after the next six years [59,84].…”
Section: Ultrafiltration Failurementioning
confidence: 99%